Straight from the horse's mouth: Increasing self‐report in mental health assessment in individuals with intellectual disability. Issue 2 (3rd November 2021) - Havercamp, Susan M.; Barnhill, L. Jarrett; Bonardi, Alexandra; Chapman, Richard A.; Cobranchi, Chelsea; Fletcher, Robert J.; Rabidoux, Paula; Seeley, John R.; Tassé, Marc J.; ,
Abstract: Background: Mental health conditions are common among individuals with intellectual disability. Under recognition of mental health disorders leading to unmet treatment needs is common in this population. This article addresses one major contributing factor, the lack of cognitively accessible self‐report measures for individuals with intellectual disability. Method: In this literature‐informed overview of the state of the field, we discuss the need for, and complexities of, including individuals with intellectual disability in mental health assessments. Results: With appropriate supports, many individuals with intellectual disability can respond to mental health questions. We discuss evidence‐based strategies to make mental health assessments more accessible. Conclusion: We highlight the need to engage individuals with intellectual disability to provide first‐hand information about their health and well‐being. New instruments and research procedures should be developed in partnership with individuals with intellectual disability. Self‐report may be essential to advancing the science of mental health research.